Muslim Tourists' Purchase Intention Of Halal Food In Türkiye - Rusydiana, Aam Slamet; Maysyaroh, Siti; Awdalkrem, Hussein (Al-Infaq: Jurnal Ekonomi Islam, 2024)
This study aims to explore the purchase intention of halal food products in Türkiye from the perspective of Muslim tourists. This study is a quantitative research using primary data. A total of 130 Muslims who have visited Türkiye became respondents and filled out this research questionnaire. The data obtained were then analyzed using the PLS-SEM method with the help of SmartPLS 3.0 software. The findings of this study indicate that halal credence and NFC (Need for Cognition) do not have a significant direct relationship with halal purchase intention. Both also have no significant indirect relationship with halal purchase intention through halal consumer attitudes as a mediating variable.